Saturation control of switched nonlinear systems. (May 2019) - Zhang, Junfeng; Raïssi, Tarek
Abstract: This paper investigates the saturation control for a class of switched nonlinear systems, where the nonlinearity function is restricted in a sector. The proposed approach is based on the theory of positive systems and a criterion is addressed to ensure the positivity property of the considered systems. The system states starting from a cone will remain in another cone. Under an average dwell time condition, a control design methodology is established in terms of linear programming. It is shown in this paper that the proposed approach can be applied for positive systems and also for a general class of nonlinear systems. Then, the saturation control synthesis of switched nonlinear systems with exogenous disturbances is addressed. Under the designed saturation controller, the states of each subsystem start from a cone and remain within it. Thus, the states of the switched systems start from a cone containing the origin and remain in another cone. Finally, the proposed methodology is applied to a nonlinear control system.